The Spectrum of Scarring in Craniofacial Wound Repair - desJardins-Park, Heather E.; Mascharak, Shamik; Chinta, Malini S.; Wan, Derrick C.; Longaker, Michael T. (Frontiers in Physiology, 2019)
Fibrosis is intimately linked to wound healing and is one of the largest causes of wound-related morbidity. While scar formation is the normal and inevitable outcome of adult mammalian cutaneous wound healing, scarring varies widely between different anatomical sites. The spectrum of craniofacial wound healing spans a particularly diverse range of outcomes. While most craniofacial wounds heal by scarring, which can be functionally and aesthetically devastating, healing of the oral mucosa represents a rare example of nearly scarless postnatal healing in humans. In this review, we describe the typical wound healing process in both skin and the oral cavity. We present clinical correlates and current therapies and discuss the current state of research into mechanisms of scarless healing, toward the ultimate goal of achieving scarless adult skin healing.